The Potential of the Indonesian Navy in Protecting Maritime Border Areas: Measurement through Mahan's Theory - Meroja, Isrofa; Zaini, Ansori; Alam, Tasdik Mustika (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia as an archipelagic country has open sea areas and the existence of the Indonesian Archipelagic Sea Lane (ALKI) which can create vulnerabilities to various possible maritime threats. The country of Indonesia, most of which is territorial waters, requires a strong Navy to maintain security and the country's territorial boundaries. The aim of this research is to see the potential of the Indonesian National Army Navy through Mahan's Theory. This research uses a qualitative method with a descriptive approach. The data collection technique in this research was carried out through searching secondary data obtained from books, articles, news, comments and government publications. The results of this research indicate that there must be an increase in the Indonesian Navy and modernization of Alusista must also be carried out.